Synthesis and Characterization of Electrochemical Properties of Manganese Ferrite Nanoparticles MnFe2O4 from Iron - Husain, Sadang; Irfansyah, Muhammad; Riyanto, Agus; Arjo, Sugianto (Program Studi Pendidikan Fisika UHAMKA, 2019)
Synthesis and characterization of the electrochemical properties of manganese ferrite nanoparticles (MnFe2O4) from iron ore have been done. The aim of this research was to determine the potential of iron ore as a source for the manufacture of MnFe2O4 and to know electrochemical characterization. The precipitation method was used in this research. Iron ore samples were taken from Tanah Laut Regency, South Kalimantan, Indonesia. The sample of iron ore was purified first to synthesis MnFe2O4 nanoparticle. Manganese salt MnCl2 is used as a source of manganese. Characterization of samples use TEM and potentiostat. Glucose oxidase (GOD) is used as a sample to be given electrochemical properties of the sample. The GOD concentration used is 0.2; 0.4; 0.6; and 0.8 ppm. The range of MnFe2O4 nanoparticles was successfully made with sample diameters ranging from 1.5 to 12.5 nm. The current values ​​obtained on MnFe2O4 nanoparticles range from 0.226 - 0.322 mA. The sensitivity of MnFe2O4 nanoparticles is around 0.16 mA/ppm. The higher the concentration used, the greater the current produced.